Tank-mix Options for Control of Tropical Soda Apple and Dogfennel - Brent A. Sellers; Jason A. Ferrell (EDIS)
SS-AGR-300, a 2-page illustrated fact sheet by B.A. Sellers and J.A. Ferrell, describes results of UF/IFAS studies of combinations of herbicides for control of dogfennel growing alongside TSA.   Published by the UF Department of Agronomy, January 2008.